Central mechanisms involved in pilocarpine-induced pressor response - Takakura, Ana C. [UNESP]; Moreira, Thiago S.; Borella, Thais L. [UNESP]; Paulin, Renata F. [UNESP]; Colombari, Debora S. A. [UNESP]; De Luca, Laurival A. [UNESP]; Colombari, Eduardo [UNESP]; Menani, José Vanderlei [UNESP] (Elsevier B.V., 2011)
Pilocarpine (cholinergic muscarinic agonist) injected peripherally may act centrally to produce pressor responses; in the present study, using c-fos immunoreactive expression, we investigated the forebrain and brainstem areas activated by pressor doses of intravenous (i.v.) pilocarpine. In addition, the importance of vasopressin secretion and/or sympathetic activation and the effects of lesions in the anteroventral third ventricle (AV3V) region in awake rats were also investigated. In male Holtzman rats, pilocarpine (0.04 to 4 mu mol/kg b.w.) i.v. induced transitory hypotension followed by long lasting hypertension. Sympathetic blockade with prazosin (1 mg/kg b.w.) i.v. or AV3V lesions (1 day) almost abolished the pressor response to i. v. pilocarpine (2 mu mol/kg b.w.), whereas the vasopressin antagonist (10 mu g/kg b.w.) i.v. reduced the response to pilocarpine. Pilocarpine (2 and 4 mu mol/kg b.w.) i.v. increased the number of c-fos immunoreactive cells in the subfornical organ, paraventricular and supraoptic nuclei of the hypothalamus, organ vasculosum of the lamina terminalis, median preoptic nucleus, nucleus of the solitary tract and caudal and rostral ventrolateral medulla. These data suggest that i.v. pilocarpine activates specific forebrain and brainstem mechanisms increasing sympathetic activity and vasopressin secretion to induce pressor response. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Cholinergic mechanisms; Arterial pressure; Hypertension; Sympathetic activity; Vasopressin